What does ELF Look like in an Indonesian EFL Context? A Critical Literature Review - Dwi Budidarma Sutrisno; Jasmal Martora (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasifik Morotai, 2024)
The scholarly discussion surrounding the implications of World English (WE) and English as a Lingua Franca (ELF) in English language teaching has been taking place for decades. As part of the expanding circle country based on Kachru's Three Concentric Circles, Indonesia considers English as a Foreign Language (EFL) and has been gradually influenced by the conceptual frameworks of WE and ELF. This study aims to critically examine the existing literature on the incorporation of ELF into EFL classrooms in Indonesia, with a focus on the following questions: (1) What are the types of ELF concepts that have been introduced to the EFL context in Indonesia? (2) How do teachers perceive and approach the incorporation of ELF in EFL classes? (3) What are the potential opportunities for incorporating ELF in the Indonesian EFL context? and (4) What are the potential challenges facing the incorporation of ELF in the Indonesian EFL context? The findings of this study reveal that the types of ELF in Indonesia can be found in code-mixing and the uniqueness of articles and plurals by Indonesian speakers of English in an ELF context. Half of the teachers observed in the studies were found to be familiar with ELF, with many potentials for implementing ELF in Indonesian EFL considering the fact that Indonesia is as a multilingual country with diverse linguistic culture, and many scholars working on policy recommendations. However, the challenges of ELF in Indonesia still exist due to the practices of native speakers' ideology in Indonesia that have arguably been implemented since the beginning of English language teaching in Indonesia.